Konseptualisasi Klinik Penegakan Hukum Pemilu dalam Penanganan Pelanggaran Pemilu Tahun 2024 - Supriyadi Supriyadi; Andi Intan Purnamasari; Darmiati Darmiati (Badan Pengawas Pemilihan Umum, 2023)
The election law enforcement clinic was introduced as an innovative endeavor to strengthen the mechanism for addressing violations in the upcoming 2024 elections. This idea emerged in response to the need for a more accountable, transparent, and violation-free election process that preserves its integrity and democratic credibility. The research conducted is a normative study that employs a legislative and conceptual approach. This study is grounded in theories of authority, concept formation, and the reality theory posited by Pierre Bourdieu. Through these theoretical lenses, the research delves deeply into the discourse on the establishment of the election law enforcement clinic. The findings indicate several crucial points. First, the authority to establish an election law enforcement clinic in Law Number 7 of 2017 is not explicitly stated. However, its regulation, which is implicit in nature, is facultative. This means that such a regulation is not binding or mandatory for implementation. Secondly, the design for the election law enforcement clinic can be developed using specific methods. Characteristics of this design include an ad hoc institutional structure, an independent position outside of Bawaslu, personnel comprising of election overseers and academics, and the utilization of a cooperation agreement as a legal instrument. Furthermore, funding for the clinic's operations can come from both Bawaslu and higher education institutions.